Trajectories of interleukin 10 and heart fatty acid-binding protein levels in traumatic brain injury patients with or without extracranial injuries - Niiranen, Toni J. U.; Chiollaz, Anne-Cécile; Takala, Riikka S. K.; Voutilainen, Miko; Tenovuo, Olli; Newcombe, Virginia F. J.; Maanpää, Henna-Riikka; Tallus, Jussi; Mohammadian, Mehrbod; Hossain, Iftakher; van Gils, Mark; Menon, David K.; et al. (Frontiers in Neurology, 2023)
Background: Interleukin 10 (IL-10) and heart fatty acid-binding protein (H-FABP) have gained interest as diagnostic biomarkers of traumatic brain injury (TBI), but factors affecting their blood levels in patients with moderate-to-severe TBI are largely unknown. Objective: To investigate the trajectories of IL-10 and H-FABP between TBI patients with and without extracranial injuries (ECI); to investigate if there is a correlation between the levels of IL-10 and H-FABP with the levels of inflammation/infection markers C-reactive protein (CRP) and leukocytes; and to investigate if there is a correlation between the admission level of H-FABP with admission levels of cardiac injury markers, troponin (TnT), creatine kinase (CK) and creatine kinase MB isoenzyme mass (CK-MBm). Materials and methods: The admission levels of IL-10, H-FABP, CRP, and leukocytes were measured within 24 h post-TBI and on days 1, 2, 3, and 7 after TBI. The admission levels of TnT, CK, and CK-MBm were measured within 24 h post-TBI. Results: There was a significant difference in the concentration of H-FABP between TBI patients with and without ECI on day 0 (48.2±20.5 and 12.4±14.7ng/mL, p=0.02, respectively). There was no significant difference in the levels of IL-10 between these groups at any timepoints. There was a statistically significant positive correlation between IL-10 and CRP on days 2 (R=0.43, p<0.01) and 7 (R=0.46, p=0.03) after injury, and a negative correlation between H-FABP and CRP on day 0 (R=-0.45, p=0.01). The levels of IL-10 or H-FABP did not correlate with leukocyte counts at any timepoint. The admission levels of H-FABP correlated with CK (R=0.70, p<0.001) and CK-MBm (R=0.61, p<0.001), but not with TnT. Conclusion: Inflammatory reactions during the early days after a TBI do not significantly confound the use of IL-10 and H-FABP as TBI biomarkers. Extracranial injuries and cardiac sources may influence the levels of H-FABP in patients with moderate-to-severe TBI.